2016
DOI: 10.1080/10508422.2016.1182025
|View full text |Cite
|
Sign up to set email alerts
|

Are Ethics Training Programs Improving? A Meta-Analytic Review of Past and Present Ethics Instruction in the Sciences

Abstract: Given the growing public concern and attention placed on cases of research misconduct, government agencies and research institutions have increased their efforts to develop and improve ethics education programs for scientists. The present study sought to assess the impact of these increased efforts by sampling empirical studies published since the year 2000. Studies published prior to 2000 examined in other meta-analytic work were also included to provide a baseline for assessing gains in ethics training effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
133
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 87 publications
4
133
1
10
Order By: Relevance
“…Deepening into the above considerations, may we note that our findings are consistent with prior research, insofar characteristics of the students themselves influence the effectiveness of instruction of ethics courses [71]. Notably, student's gender influences course effectiveness: men tend to have a lower start level of ethical awareness; they can be expected to have larger gains from these courses than women [71].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Deepening into the above considerations, may we note that our findings are consistent with prior research, insofar characteristics of the students themselves influence the effectiveness of instruction of ethics courses [71]. Notably, student's gender influences course effectiveness: men tend to have a lower start level of ethical awareness; they can be expected to have larger gains from these courses than women [71].…”
Section: Discussionsupporting
confidence: 86%
“…More specific practical implications suggest the delivery of ethics/CSR instructional content using multiple expert trainers, integrated cases, and practice activities that encourage active trainee participation, thus benefiting student learning, ideas consistent with the extant literature, as e.g., Watts et al [71] found out in their meta-analysis of ethics programmes in science disciplines. Moreover, regarding the importance of students' active participation in business ethics/CSR programmes, courses should have a clear focus and avoid dispersion, including a diversity of relatively short and frequent-both individual and group-based-practice activities.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Historically, most efforts at improving research integrity have focused on either the education or socialization of individual, typically junior, researchers through courses in ethics or the “responsible conduct of research,” (National Academies 2009; Watts et al 2016) on the one hand, and a reliance on organizational “whistle-blowers,” on the other hand (Devine 1995; Redman and Caplan 2015; Mecca et al 2014). Yet, there is an increasing recognition among those concerned with fostering and sustaining research activity that these remedies, though important and necessary, are not sufficient to attain the objective.…”
Section: Discussionmentioning
confidence: 99%